2016
DOI: 10.1103/physrevb.94.035159
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of constrained density functional theory

Abstract: Constrained density functional theory (cDFT) is a versatile electronic structure method that enables ground-state calculations to be performed subject to physical constraints. It thereby broadens their applicability and utility. Automated Lagrange multiplier optimisation is necessary for multiple constraints to be applied efficiently in cDFT, for it to be used in tandem with geometry optimization, or with molecular dynamics. In order to facilitate this, we comprehensively develop the connection between cDFT en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…In an effort to reconcile the valence state measurements with the magneto-thermal measurements, we have applied density functional theory (DFT) methods including SOC, correlation effects, and a fixed atomic spin moment method in our study of Li 2 OsO 3 (see Methods for the description) 4752 . Without magnetism, SOC is strong enough to provide a pseudogap but no gap, within the Os t 2g bands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to reconcile the valence state measurements with the magneto-thermal measurements, we have applied density functional theory (DFT) methods including SOC, correlation effects, and a fixed atomic spin moment method in our study of Li 2 OsO 3 (see Methods for the description) 4752 . Without magnetism, SOC is strong enough to provide a pseudogap but no gap, within the Os t 2g bands.…”
Section: Resultsmentioning
confidence: 99%
“…A mesh of 9 × 5 × 9 was used for k-sampling and 500 eV for energy cutoff. The constrained atomic spin moment on Os method 52 was used in some calculations to fix moments at or near the observed value. Constraints are managed by the use of Lagrangian multipliers, imposed with constraint parameters; the input parameter λ  = 1.0 was used 48 .…”
Section: Methodsmentioning
confidence: 99%
“…In the above expression, the function c depends on ξ parametrically: for any fixed value of ξ, the inner loop minimization of the Kohn-Sham energy produces a unique density ρ(r) and hence a new value of c. According to Eq. (7), the outer loop energy maximization can be viewed as a root finding problem that can be terminated when a value of ξ is found that satisfies max |c(ξ)| ≤ ε at some fixed convergence threshold ε. O'Regan and Teobaldi 43 have analyzed the necessary conditions to guarantee the uniqueness of this solution. The Newton-Raphson method can be applied to iteratively solve the root finding problem by generating a new guess for ξ n at step n according to…”
Section: B Configuration Interaction Based On Constrained Dftmentioning
confidence: 99%
“…, the Lagrange multipliers. Apart from being simple, the constraint terms in equation (10) are linear in the density, thus avoiding multiple stationary solutions and/or energy discontinuities [26].…”
Section: Noncollinear Constrained Spin-dftmentioning
confidence: 99%